Growth and yield performance of some exotic clones of Hevea brasiliensis in North Kerala region - Lakshmanan, Radha; Meenakumari, T.; Chandrasekhar, T.R.; Nazeer, M.A. (Journal of Plantation Crops, 2014)
The growth and yield performance of a set of exotic clones from Malaysia and Ivory Coast was evaluated in comparison with RRII 105, a popular high yielding indigenous clone, for their adaptability in the northern tract of Kerala. The region is characterised by absence of sufficient summer showers and relatively long dry spells. Analysis of growth up to 16 years after planting revealed significant clonal differences in growth pattern, only from the 10th year of planting. Girth and girth increment was the highest in IRCA 130, followed by PB 330. The lowest girth was observed in RRIM 703. The clone IRCA 130 also exhibited significantly high annual and summer yield followed by PB 255. Peak rubber yield was recorded in the month of September irrespective of clones. IRCA 130 showed significantly superior branching height and bole volume followed by PB 255. Incidence of tapping panel dryness (TPD) and pink disease in IRCA 130 was comparable to clone RRII 105. The suitability of the newly introduced clones for the region is discussed.